Sistem Pendukung Keputusan Pemilihan Laptop Untuk Mahasiswa Arsitektur Dengan Metode SAW - Herald, Grace Gabriella; Saputro, Daniel Tunggono; Saragi, Yeremia Chris (Politeknik Indonusa Surakarta, 2021)
With the development of the era at this time, the needs needed as a student also develop and increase, as well as students in the Department of Architecture. The technology needs of architecture students, in this case a laptop, is quite necessary to support the needs in the field of architecture. With a variety of laptop brands and different specifications, of course, architecture students will be more selective in deciding to buy a laptop that is suitable for supporting architectural needs. Based on this, to assist architecture students in choosing a laptop, it is necessary to have a decision-making system using the SAW (Simple Additive Weight) method. This method is used to determine alternative choices based on predetermined weights and criteria. And then sorting is done which will determine the best alternative from all existing criteria, namely a laptop that fits the needs and desires of architecture students. In this study, 6 alternative choices of laptop brands are given, namely Asus, Acer, Dell, Lenovo, MSI and HP. After normalizing for each criterion and multiplying the results of normalization with the weight of the criteria, a laptop that is suitable for architecture students is obtained.